PRÁTICAS SUSTENTÁVEIS E ATIVIDADES AMBIENTAIS, ECONÔMICAS E SOCIAIS DE EMPRESAS PORTUÁRIAS E O IMPACTO NA COMUNIDADE LOCAL DO MUNICÍPIO DE PARANAGUÁ-PR - Franco, Luciane Silva (2020)
The purpose of this study is to analyze the sustainable practices and activities of the port companies in the city of Paranaguá-PR and the environmental, social, and economic impacts on the local community. The Methodi Ordinatio methodology was employed to conduct the literature review, and the analysis encompassed the 2002-2020 period in the databases Scopus, ScienceDirect, and Web of Science. The portfolio of the study comprised 50 papers. The mixed method was employed, with the application of a questionnaire adapted from the Ethos Institute (2017) to the residents of Paranaguá-PR and interviews conducted with the managers of port companies. The main results of the quantitative research point to a high negative impact among the respondents concerning the questions related to the environmental, economic, and social scopes. The questions most cited as negative due to the companies’ operations were: in the environmental scope, residues from cargo transportation that might generate odor emissions; in the economic scope, the land transportation that deteriorates asphalt roads; and in the social scope, the potential health and welfare hazards to the community in the area. The groups analyzed present significant variability. The significant variables were gender, age, level of education, time living in the city, and distance between the residence and the port area. The qualitative research, through interviews with the managers of port companies in Paranaguá-PR, revealed that certain companies present environmental certification and that there is a concern with the environmental impact caused by their operations, such as dust, residues, noises, traffic jams, and bad odors in the region. However, in practice, they have found challenges in the solution to those problems due to poor communication between the companies and federal, state, and municipal policies. In the economic aspects, even though they advance the economy of the region, port companies end up allocating financial resources to social development projects (education, healthcare or leisure) that benefit only their teams of collaborators. Few companies reported social projects geared towards the external community, and the donation projects have presented nothing concrete. Therefore, the results reveal that the environmental and social sustainability practices adopted by the port companies of Paranaguá-PR, despite being performed to fulfill the legislation, need to be rethought by the managers so as to contribute to the reduction of costs and the appreciation of collaborators and town residents. No evidence was found, among companies and residents, of the sustainability based on the Triple Bottom Line.